Analisis Kelayakan Ekonomi "Pembangunan Kereta Gantung Sebagai Penunjang Pariwisata di Kota Batu" - Bobby Marian Rizal Supryadi; Muhammad Sri Wahyudi Suliswanto; Setyo Wahyu Sulistyono (Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the feasibility of the cable car project to be implemented in Batu City. This type of research is quantitative which is assisted by primary and secondary data in processing data. Primary data in the form of the latest numbers in 2021 assisted by Microsoft Excel Software. The analysis method of this research is an investment feasibility analysis using NPV, IRR, Net B/C Ratio, Payback Period, ROI, and Sensitivity Analysis instruments. This study found that the cable car project was declared feasible to be built with an NPV value of Rp. 221,270,812,352, IRR 14.90%, Net B/C Ratio 14.90%, Payback Period estimated at 22 Years 7 Months and RIO 13.90%. Sensitivity analysis of 75% of the number of visitors stated that the NPV of Rp. -29,045,541,406, IRR of 10.05%, Net B/C Ratio of 10.83%, Payback Period . 24 Years 7 Months, and an ROI of 9.83%.